Production and characterisation of cellulase from Bacillus pumilus EB3 - Ariffin, Hidayah; Abdullah, Norhafizah; Md. Shah, Umi Kalsom; Shirai, Yoshihito; Hassan, Mohd Ali (Federation of Engineering Institutions of Islamic Countries, 2006)
Cellulase production from bacteria can be an advantage as the enzyme production rate is normally higher due to bacterial high growth rate. Screening of bacteria, optimisation of fermentation conditions and selection of substrates are important for the successful production of cellulase. This study is conducted to produce cellulase from our local isolate Bacillus pumilus EB3, using carboxymethyl cellulose (CMC) as substrate. Following that, cellulase produced from Bacillus pumilus EB3 was purified using ion exchange chromatography with anion exchanger (HiTrap QXL) for characterisation of the cellulase. Cellulase was successfully produced in 2L stirred tank reactor (STR) with the productivity of 0.53, 3.08 and 1.78 U/L.h and the maximum enzyme activity of 0.011, 0.079 and 0.038 U/mL for FPase, CMCase and β-glucosidase respectively. Purification of cellulase from Bacillus pumilus EB3 using ion exchange chromatography showed that 98.7% of total CMCase was recovered. Protein separation was however based on subtractive separation where the contaminants were bound to the column instead of CMCase. Characterisation of the enzyme found that CMCase from Bacillus pumilus EB3 has a molecular weight range from 30-65 kDa and was optimally active at pH 6.0 and temperature 60°C. The CMCase also retained its activity over a wide pH range (pH 5.0–9.0) and temperature range (30-70°C).